Study of the main characteristics of polystyrene and phenol-formaldehyde resin waste - Khudayberdiev, Nosirjon; Ergashev, Oybek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This study investigates the physicochemical properties of phenol-formaldehyde resin (PFR) and polystyrene (PS) waste as promising secondary resources for the production of carbon-based adsorbents. A comparative analysis of density, thermal stability, permeability, and mechanical strength was conducted. The results show that PFR, due to its high thermal resistance and dense crosslinked structure, is better suited for the synthesis of microporous carbon materials, while PS, with its lower density and higher permeability, is advantageous for obtaining meso- and macroporous structures. The findings highlight the potential for the effective recycling of polymeric waste into functional adsorbents for environmental protection.